Preliminary gastroprotective effect of aqueous Bixa orellana leaf extract in an HCl/ethanol‑induced gastric ulcer rat model - Asma Syuhaily Mohd Yusof; Yoke Keong Yong; Lai Yen Fong; Chin Theng Ng; Shiran Mohd Sidik; Saidi Abdul Moin; Mohd Sofian Omar Fauzee; Muhammad Nazrul Hakim Abdullah; Zuraini Ahmad (Life Sciences, Medicine and Biomedicine, 2026)
Gastric ulceration develops when aggressive luminal factors overwhelm gastric mucosal defense. Bixa orellana leaves are used traditionally for gastrointestinal complaints, but direct evidence for aqueous B. orellana leaf extract (BOE) in chemically induced gastric ulcer models remains limited. This exploratory study evaluated the effects of aqueous BOE against HCl/ethanol-induced gastric ulceration in rats. Twenty-four male Sprague-Dawley rats were allocated to four groups (n = 6/group): untreated ulcer control, omeprazole 100 mg/kg, BOE 50 mg/kg, and BOE 150 mg/kg. Treatments were administered orally for 7 days. After 24 h fasting, ulcers were induced with 1.0 mL HCl/ethanol, and stomach tissues were collected for macroscopic ulcer-index scoring and hematoxylin and eosin histological assessment. No measured outcome reached statistical significance. The ulcer index showed a non-significant overall difference among groups (Kruskal-Wallis H = 6.57, p = 0.087). Histological scores were also non-significant for congestion (p = 0.458), edema (p = 0.158), inflammatory infiltration (p = 0.126), and necrosis (p = 0.089). Omeprazole and BOE 150 mg/kg showed numerically lower ulcer-index values than the untreated ulcer control, whereas BOE 50 mg/kg remained close to the ulcer control. BOE 150 mg/kg also showed numerically lower edema, inflammatory infiltration, and necrosis scores, but these differences were not statistically confirmed. The present study demonstrates biological trends rather than statistically confirmed gastroprotective efficacy. Aqueous BOE showed a possible dose-related gastroprotective trend, with 150 mg/kg producing the most favorable numerical pattern. Larger dose-response studies with extract standardization, blinded morphometric assessment, ulcer-area and mucus endpoints, and biochemical assays are required before efficacy or mechanistic claims can be made.